Endoscopic ultrasound for structured surveillance after curative treatment of esophageal cancer - Bohle, Wolfram; Nowack, Lioba; Schaudt, Andre; Koeninger, Joerg; Zoller, Wolfram G.; Albert, Jörg G. (Zeitschrift für Gastroenterologie, 2024)
Background Structured surveillance after treatment of esophageal cancer is not established. Due to a paucity of data, no agreement exists on how surveillance should be performed. The main argument against intensive follow-up in esophageal cancer is that it may not lead to true survival advantage.Methods Structured surveillance was performed in 42 patients after multimodal therapy with peri-operative chemotherapy (29) or definitive chemoradiotherapy (13) of esophageal cancer. The surveillance protocol included gastroscopy, endoscopic ultrasound, chest X-ray, abdominal ultrasound, and CEA measurement at regular intervals of up to five years. We analyzed relapse rate, time to relapse, localization of recurrence, diagnosis within or without structured surveillance, diagnostic method providing the first evidence of a relapse, treatment of recurrence, and outcome.Results Median follow-up was 48 months; 18/42 patients suffered from tumor relapse, with 16 asymptomatic patients diagnosed within structured surveillance. Median time to recurrence was 9 months. Isolated local or locoregional recurrence occurred in 6, and isolated distant relapse in 9 patients. All patients with isolated locoregional recurrence were exclusively diagnosed with endoscopic ultrasound. Six patients received curatively intended therapy with surgery or chemoradiation, leading to long-lasting survival.Conclusion Structured surveillance offers the chance to identify limited and asymptomatic tumor relapse. Especially in cases of locoregional recurrence, long-lasting survival or even a cure can be achieved. Endoscopic ultrasound is the best method for the detection of locoregional tumor recurrence and should be an integral part of structured surveillance after curative treatment of esophageal cancer.
Keywords: esophageal cancer; surveillance; endoscopic ultrasound; locoregional tumor recurrence; follow-up